The Diagnostic Value of Anti-Cyclic Citrullinated Peptide Antibodies (anti-CCP) in Patients with Rheumatoid Arthritis - Damjanovska, LJubinka; Anastasovska, Violeta; Gruev, Todor (Centre for Evaluation in Education and Science (CEON/CEES), 2007)
A cross-sectional study was carried out to analyze the prevalence of anti-CCP antibodies and IgM RF in the sera of 160 randomly selected patients from the Rheumatology Department: 60 with RA, 50 with other rheumatic diseases (non-RA), 50 healthy controls (HC). The mean age of the group was 50.06+/–11.9 years. There were 141 females (88.1%) and 19 males (11.9%). RA patients fulfilled the revised ACR criteria. The mean duration of the disease was 82.4 months. Anti-CCP ELISA kit and IgM RF Latex test were used. The mean anti-CCP values were as follows: RA 60.4+/–57.6, non-RA 2.1+/–3.6, HC 1.3 +/–0.4 U/mL. Respectively, the mean values of IgM RF were: RA 515.8+/–525, non-RA 102+/–294, HC 15+/–57.5. Forty out of 60 (66.6%) RA patients were anti-CCP positive. Forty one out of 60 (68.3%) RA patients were positive for IgM RF. As expected, anti-CCP showed comparable sensitivity (66.8% vs. 68.3%) and higher specificity (98% vs. 87%) than IgM RF, at optimal cut-off values. The presence of either anti-CCP or IgM RF increased the testing sensitivity for the diagnosis of RA to 76.6%. AUC was greater for anti-CCP than for IgM RF (0.92 vs. 0.82).